2016
DOI: 10.1039/c6tb00006a
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading inhibits hypertrophy in chondrogenically differentiating hMSCs within a biomimetic hydrogel

Abstract: Three dimensional hydrogels are a promising vehicle for delivery of adult human bone-marrow derived mesenchymal stem cells (hMSCs) for cartilage tissue engineering. One of the challenges with using this cell type is the default pathway is terminal differentiation, a hypertrophic phenotype and precursor to endochondral ossification. We hypothesized that a synthetic hydrogel consisting of extracellular matrix (ECM) analogs derived from cartilage when combined with dynamic loading provides physiochemical cues for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 81 publications
(97 reference statements)
2
44
0
1
Order By: Relevance
“…Gels were placed in free swelling conditions or in custom bioreactors that were set to apply a compressive strain in a sinusoidal waveform from 0 to 5% at 1 Hz for 1 hour per day. This loading regime was chosen based on previous studies that have shown in PEG hydrogels, the chondrocyte phenotype is maintained and the ECM synthesized is similar or enhanced when compared to free swelling across different donors and cell types (i.e., primary and stem cells) (Aisenbrey and Bryant, 2016; Farnsworth et al, 2013). Medium was replaced every two days for 9 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gels were placed in free swelling conditions or in custom bioreactors that were set to apply a compressive strain in a sinusoidal waveform from 0 to 5% at 1 Hz for 1 hour per day. This loading regime was chosen based on previous studies that have shown in PEG hydrogels, the chondrocyte phenotype is maintained and the ECM synthesized is similar or enhanced when compared to free swelling across different donors and cell types (i.e., primary and stem cells) (Aisenbrey and Bryant, 2016; Farnsworth et al, 2013). Medium was replaced every two days for 9 days.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the presence of dynamic compressive loading, which is present in the native environment, is an important parameter in cartilage tissue engineering (Butler et al, 2000). Recent studies have identified physiologically relevant loading regimes that support the chondrogenic phenotype and cartilage-specific ECM deposition in PEG hydrogels (Aisenbrey and Bryant, 2016; Farnsworth et al, 2013). Collectively these and other studies support the use of PEG hydrogels for applications in cartilage tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) ChS is the main glycosaminoglycan in cartilage and creates a unique environment that is hyperosmotic and promotes tissue synthesis, especially under dynamic compression. (17) RGD, a cell adhesion peptide, provides a mechanism for cells to sense substrate stiffness and acts as a mechanosensor to cells activating integrin α5β1.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…It has been detected that moderate amplitude strains (5%) applied at 1 Hz stimulate chondrogenesis of hMSCs and enable stable chondrocyte-like phenotype, while higher strains and lower frequencies have a negative effect on chondrogenesis [95].…”
Section: Bioreactors As Biomimetic System Componentmentioning
confidence: 99%